Madrasah Tsanawiyah Teachers' Perceptions of Blended Learning Implementation within Islamic Educational Institutions - Yanto, Subari; Arbain; Sakri Abdullah (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2024)
Although the concept of blended learning is widely recognized, many teachers, particularly those at Madrasah Tsanawiyah (MTs), remain unfamiliar with its principles and methods of implementation. In response, the Ministry of Religious Affairs of the Republic of Indonesia, through the Education and Training Agency in Makassar, organized training for MTs teachers on blended learning. This study aimed to examine the perceptions of Madrasah Tsanawiyah teachers regarding the use of blended learning in Civic and Environmental Education. Adopting a descriptive quantitative approach, the study involved a population of 120 teachers, participants in the training, which was divided into five different classes. Using purposive sampling, a sample of 29 teachers was selected, focusing on those teaching Civic Education. Data was collected through a questionnaire and analyzed descriptively, with results categorized into five groups. The findings revealed that teachers’ perceptions of blended learning were generally positive, with a mean score of 3.6, categorized as